2021
DOI: 10.1021/acs.est.0c08179
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Thermocatalytic and Photo/Thermocatalytic Oxidation for VOCs Purification over Manganese-based Oxide Catalysts

Abstract: Volatile organic compounds (VOCs) are one of the main sources of air pollution, which are of wide concern because of their toxicity and serious threat to the environment and human health. Catalytic oxidation has been proven to be a promising and effective technology for VOCs abatement in the presence of heat or light. As environmentally friendly and low-cost materials, manganese-based oxides are the most competitive and promising candidates for the catalytic degradation of VOCs in thermocatalysis or photo/ the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(89 citation statements)
references
References 182 publications
1
88
0
Order By: Relevance
“…The positive synergistic effect due to the addition of a small amount of zirconia on the MnO x and the solar multi-catalytic approach led to obtaining a low toluene T 90 , considering the absence of noble metals co-catalysts. The obtained value of T 90 with the MnO x -5% ZrO 2 sample (180 • C) is comparable or lower with respect to the other MnO xbased catalysts reported in the literature (in the range 200 • C-270 • C considering an initial toluene concentration of 1000 ppm [20,37]).…”
Section: Photocatalytic Thermocatalytic and Photothermo-catalytic Removal Of Toluene In Gas Phasesupporting
confidence: 64%
See 1 more Smart Citation
“…The positive synergistic effect due to the addition of a small amount of zirconia on the MnO x and the solar multi-catalytic approach led to obtaining a low toluene T 90 , considering the absence of noble metals co-catalysts. The obtained value of T 90 with the MnO x -5% ZrO 2 sample (180 • C) is comparable or lower with respect to the other MnO xbased catalysts reported in the literature (in the range 200 • C-270 • C considering an initial toluene concentration of 1000 ppm [20,37]).…”
Section: Photocatalytic Thermocatalytic and Photothermo-catalytic Removal Of Toluene In Gas Phasesupporting
confidence: 64%
“…Interestingly also for the removal of ethanol, the multi-catalytic reaction (i.e., the photothermo-catalysis) allowed us to improve the performance related to ethanol oxidation (Table 6, Figure S5). With MnO x -5%ZrO 2 , the T 90 of ethanol conversion was lowered to 34 • C (154 • C), a value that is comparable or lower, considering an initial ethanol concentration of 1000 ppm, with respect to the other MnO x -based materials reported in the literature (in the range 127 • C (initial ethanol concentration of 300 ppm) −200 • C (initial ethanol concentration of 600-1945 ppm) [37,40]). The total oxidation to CO 2 was favoured on this sample, and for this reason, the maximum conversion to acetaldehyde was low (35% at 118 • C), with a decrease of 205 • C of the T 90 related to the conversion to CO 2 compared to the thermocatalytic tests.…”
Section: Maximum Conversion To Acetaldehydementioning
confidence: 82%
“…The oxidative and catalytic performance of manganese oxides can be affected by various structural factors including crystal phases, morphologies, crystal facets, and structural dimensionalities [ 48 ]. For instance, Huang et al reported that -MnO 2 showed higher oxidative activity than MnO 2 on bisphenol A oxidation due to the occurrence of more accessible active sites in layered -MnO 2 than other tunnel structured MnO 2 [ 49 ].…”
Section: Effect Of Structure On the Reactivity Of Mn(iii) (Oxyhydr)oxidesmentioning
confidence: 99%
“…In Figure 10, the possible mechanistic pathway based on the earlier discussion is concluded. [38] During the PTC process, the hybrid CuO x clusters can form a Schottky barrier with TiO 2 to capture the photogenerated electrons and then hinder charge carrier recombination. In addition, the incorporation of low-valence Cu atoms can narrow the bandgap by generating the defect energy level and Cu 3d orbitals, which form band-edge excitons and enhance the separation efficiency of electronÀhole pairs.…”
Section: Mechanism Investigationmentioning
confidence: 99%